교모세포종에 대한 통합암치료의 치료 효과 증례보고 - 양진성; 장혁준; 송시연; 박지혜; 박소정; 유화승; Yang, Jin-sung; Jang, Hyuk-jun; Song, Si-yeon; Park, Ji-hye; Park, So-jung; Yoo, Hwa-seung (대한한방내과학회지, 2022)
Objective: The purpose of this report is to present the effects of integrative cancer treatment (ICT) on a patient diagnosed with glioblastoma multiforme (GBM). Methods: A 71-year-old male GBM patient received ICT from May 14 to October 12, 2021 and concurrently received temozolomide and radiotherapy. The effect on symptoms was evaluated using a visual analog scale (VAS), and changes in tumor size were assessed using magnetic resonance imaging. Results: After treatment, the VAS score for nausea decreased from 5 to 1, and the tumor size also reduced. Conclusion: ICT could be effective in treating GBM patients by reducing the size of the tumor as well as alleviating the side effects.